Fiqh Contracts for BPJS Ketenagakerjaan Syariah: A Conceptual Approach to Wakalah bil Ujrah, Wakalah bil Istithmar, and Tabarru' - Mimma Maripatul Uula; Aam Slamet Rusydiana; Siti Maysyaroh Siti Maysyaroh (Jurnal Jamsostek, 2025)
This research aims to examine fiqh contracts applicable to BPJS Ketenagakerjaan Syariah using a qualitative library research approach. Currently, the implementation of BPJS Ketenagakerjaan Syariah remains limited to the Province of Aceh; therefore, this study discusses the application of sharia principles within BPJS Ketenagakerjaan from a conceptual and normative perspective. The findings indicate that several contracts are relevant for BPJS Ketenagakerjaan Syariah, including Wakalah bil Ujrah, Wakalah bil Istithmar, and Tabarru’. These contracts play an important role in Islamic finance, particularly in the context of Islamic insurance, as they support compliance with sharia principles, including the prohibition of usury (riba), uncertainty (gharar), and gambling (maysir). In addition, these contracts reflect key Islamic values such as mutual assistance, solidarity, and fairness in the distribution of risks and benefits among participants. However, the application of these contracts in BPJS Ketenagakerjaan Syariah faces several challenges, including varying interpretations, the need for a clearer framework, and a better understanding of tax implications. Overall, these concepts provide a strong foundation for the development of a sustainable and inclusive Islamic financial system, and their effective implementation requires improved understanding and closer collaboration between financial practitioners, regulators, and ulama.